Design and Experiment of a Low-Damage Threshing Drum for Corn with Stepless Taper Adjustment - Linfeng Chen; Lei Zhang; Le Li; Lihua Zhang (Agriculture)
Aiming to improve the existing corn cylindrical drum threshing process, where the high-frequency impact of threshing elements and rubbing actions result in a high kernel breakage rate, a radial telescopic drum taper adjustment method was proposed, and a corn conical threshing drum was developed. The threshing process was analyzed by combining theory and simulation, and the conical drum enabled rapid threshing and timely penetration of the grains through the sieve, reduced the damage caused by high-frequency action on the grains, and improved the uniformity of the distribution of the discharged material. The response surface test was carried out with the drum speed, feeding quantity, and large end diameter of the drum as the influencing factors and the damage rate as the evaluation index. The results showed that when the rotating speed of the drum was 340 r/min, the feeding quantity was 2.277 kg/s, the diameter of the big end was 506.7 mm, and the breakage rate was 2.826%. The threshing effect was found to be better than when using a cylindrical drum. The research results can provide a reference for low-damage and high-efficiency harvesting of grain.